Effect of titanium dioxide nanotubes incorporated into conventional glass ionomer cement on L. acidophilus - Sena, Layse de Góis; Meyer, Maria Davoli; Ricardo, Mariana Gallante; Araújo, Isaac Jordão de Souza; Rontani, Julia Puppin; Pecorari, Vanessa Arias [UNESP]; Martinez, Elizabeth Ferreira; Teixeira, Lucas Novaes; Nociti-Junior, Francisco Humberto; Lisboa-Filho, Paulo Noronha [UNESP]; Kantovitz, Kamila Rosamilia (FapUNIFESP (SciELO), 2025)
The present in vitro study evaluated the effect of titanium dioxide nanotubes (nTiO2) incorporated into glass ionomer cement (GIC) on the growth and viability of Lactobacillus acidophilus (L. acidophilus). GIC (Ketac Molar EasyMix® = KM) was added to concentrations of 0%, 3%, 5%, 7% by weight of nTiO2 (20 nm in size). L. acidophilus strains (1x108 CFU/mL) were cultivated on GIC discs with or without the addition of nTiO2 for 1, 3 and 7 days, and the following parameters were evaluated: inhibition zone (mm) (n = 6); cell viability (Live/Dead) (n = 6); cell morphology (SEM) (15 KV, 2000X, n = 3). The data were submitted to ANOVA and the Tukey and Dunnett tests (α = 0.05). Regarding the agar diffusion test, there was no difference between GIC and the groups containing nTiO2 (p > 0.05). As for bacterial viability, the percentage of viable bacteria was lower for GIC+7% nTiO2 (p ≤ 0.05). There was no difference in the percentage of non-viable bacteria (p > 0.05). In addition, the morphology of L. acidophilus did not change in the presence of nTiO2. It can be concluded that the incorporation of titanium dioxide nanotubes into GIC, particularly at 5%, reduced L. acidophilus viability, and might hence interfere negatively with the initial colonization process of the bacterial biofilm.